High-temperature adaptive and robust ultra-thin inorganic all-solid-state smart electrochromic energy storage devices. (August 2019) - Liu, Lei; Du, Kai; He, Zhibing; Wang, Tao; Zhong, Xiaolan; Ma, Teng; Yang, Jiaming; He, Yingchun; Dong, Guobo; Wang, Shunhua; Diao, Xungang
Abstract: Electrochromic energy storage devices (EESDs) that offer high energy and power densities are extremely desirable for use in applications ranging from civilian portable electronic devices to building windows. However, the performace of EESDs under high temperature is still a big challenge because of unavoidable performance decays and the invevitable damage of components. Herein, we demonstrate an ultra-thin inorganic all-solid-state smart EESD by incorporating two complementary electrochromic materials into the electrodes. The synergy of the inorganic layers enabled the EESD to withstand a wide temperature range (20 °C-75 °C). Impressively, the volume capacitance of the EESD increased as the temperature was increased, suggesting that the EESD possess excellent adaptability to high temperatures. More importantly, the EESD exhibited outstanding capacity retention and cycling ability when operated at progressively varied temperatures. The volume capacitance of the EESD remained at 96.2% of its initial value after 2000 cycles even at 75 °C. This performance was better than most energy storage devices at high-temperatures. Additionally, obvious chromatic transition occurred during the charge/discharge process and the maximum transmittance difference between different states of the EESD reached up to 49% at 75 °C. We envision that our research provides a novel route to realize the coincident utilization of optical-electrochemical energy. Graphical abstract: An ultrathin all-inorganic smart electrochromic energy storage device (EESD) was constructed by incorporating two complementary electrochromic materials into the electrodes. The introduction of inorganic electrolyte not only ensures the EESD withstand a wide voltage window, but also significantly decreases the volume of the whole device. The EESD possesses excellent adaptability to high temperature (20 °C-75 °C) and exhibits outstanding capacitance retention during its operation at progressively varied temperatures. Furthermore, the energy storage level of the EESD could be monitored by a visual color inspection.Image 1 Highlights: The all-inorganic nature significantly decreases the volume of the whole device. The EESD possesses excellent adaptability to high temperature and can withstand a harsh temperature. The EESD exhibits outstanding capacitance retention and cycling ability during its operation. Obvious chromatic transition occurs during charge/discharge process even at high temperature.